Kebebasan Perempuan dalam Novel Akibat Menabukan Seks karya Ester Pandiaga: Kajian Feminisme - Muslimin, Muslimin; Usman, Indah Nursafitri (Jurnal Bahasa, Sastra, dan Budaya, 2024)
Literary works are not only created to express a rear opinion about a problem, but its nature frees writers and writers to argue about any problems such as politics, economics, education, community stories, even at the gender level. Feminism is part of a literary work whose theory criticizes equality that needs to be judged equally between men and women in any way. This research uses descriptive qualitative methods with Michael Foucault's approach to examine pieces of text which are then analyzed for their meaning using feminist theory.